Jardines Kitagata, Gifu (Japón) - Schwartz, Martha (2001)
<Jardines temáticos> insertos en el espacio comunitario intersticial del bloques de apartamentos
Keywords: JAPON; GIFU; PARQUES RECREATIVOS; PARQUES INFANTILES; JUEGOS INFANTILES; FUENTES; ESPACIO PUBLICO